2017
DOI: 10.1038/cddis.2017.509
|View full text |Cite
|
Sign up to set email alerts
|

MBD2 upregulates miR-301a-5p to induce kidney cell apoptosis during vancomycin-induced AKI

Abstract: Despite DNA methylation occurred in acute kidney injury (AKI), how it influenced progression of AKI remains unclear. Methyl-CpG-binding domain protein 2 (MBD2), a protein readers of methylation, was used to analyze the impact of DNA methylation on vancomycin (VAN)-induced AKI. Here, in cultured human kidney tubular epithelial cells (HK-2), we show that knockdown of MBD2 by siRNA attenuated VAN-induced apoptosis, caspase activity, and the expression of BAX and cleaved caspase 3. Interestingly, knockdown of MBD2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(86 citation statements)
references
References 44 publications
6
79
0
Order By: Relevance
“…However, a previous study reported that autophagy led to cell death in cisplatin-treated proximal tubular cells (30), whereas another study found that pharmacologic inhibition of autophagy promoted apoptosis in the same cell line and experimental model (40). A possible explanation is that nonspecific pharmacologic inhibitors of autophagy may cause unwanted side effects (18). To overcome these drawbacks, both Atg7-deficient MEF cells and PT-Atg7-KO mice were established in this study.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, a previous study reported that autophagy led to cell death in cisplatin-treated proximal tubular cells (30), whereas another study found that pharmacologic inhibition of autophagy promoted apoptosis in the same cell line and experimental model (40). A possible explanation is that nonspecific pharmacologic inhibitors of autophagy may cause unwanted side effects (18). To overcome these drawbacks, both Atg7-deficient MEF cells and PT-Atg7-KO mice were established in this study.…”
Section: Discussionmentioning
confidence: 95%
“…TUNEL and quantification were also conducted in accordance with previous studies (15,17). Morphologic analyses and flow cytometry (FCM) of apoptosis and caspase activity were performed by staining the cells with Hoechst 33342 and enzymatic assay, respectively, as previously described (17)(18)(19).…”
Section: Renal Function Morphologic Studies and Apoptosismentioning
confidence: 99%
“…To detect tissue injury, mice kidney tissues were fixed in 4% paraformaldehyde buffer for 24 hr and embedded in paraffin. Subsequently, paraffin blocks were cut into 2‐μm sections and then subjected to routine H&E, PAS, and TUNEL staining according to previously described protocols (Wang, Li, et al, ; You et al, ; Zhang, Liu, et al, ). Histological differences among the groups were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, p53 has been shown to induce apoptosis via miR‐192‐5p in wild‐type mice, which was suppressed in p53‐KO mice 86 . Blocking miR‐301a‐5p 85 or inhibiting miR‐192‐5p 86 with respective antisense oligonucleotides ameliorated VIKI in C57BL/6 mice.…”
Section: Mechanisms Of Vikimentioning
confidence: 99%
“…The miRNA appears to be an important part of this VIKI mechanistic pathway. The miRNAs miR‐301a‐5p and miR‐192‐5p have been implicated in the development of VIKI through methyl‐CpG‐binding domain protein 2 (MBD2) and p53 85, 86 . Methyl‐CpG‐binding domain proteins, are protein readers of methylation and are actively involved in DNA‐methylation‐mediated transcriptional regulation by binding to methylated CpG on the DNA and either blocking other protein factors from binding to DNA or by binding to promoters of actively transcribed genes 87 .…”
Section: Mechanisms Of Vikimentioning
confidence: 99%